Effect of pH on the properties of eggshell-derived hydroxyapatite bioceramic synthesized by wet chemical method assisted by microwave irradiation. Issue 7 (1st April 2021) - Goh, Kian Wei; Wong, Yew Hoong; Ramesh, S.; Chandran, Hari; Krishnasamy, S.; Ramesh, S.; Sidhu, Amritpal; Teng, W.D.
Abstract: In the present work, the eggshell-derived hydroxyapatite (HA) powder was successfully synthesized by a simple wet chemical method assisted by microwave irradiation. Different pH values (8, 9, 10, 11 and 12) has been investigated in order to determine their effect on the HA properties. The derived powders were characterized by XRD, FTIR, FESEM and EDX. The results showed that the pH value of the reaction is an important parameter in altering the particle size and morphology of HA. A well-formed needle-like HA particle was obtained at pH 10 with approximately 10–15 nm in width and 60–80 nm in length. Further increased in the pH, however resulted in the formation of a more rounded nanoparticles. The plausible mechanism of HA formation as a function of pH has been deliberated. The study has demonstrated that the use of biowaste eggshells as the calcium source coupled with microwave irradiation were effective in producing stoichiometric nano HA particles suitable for biomedical application.